Mathematical Creative Thinking Ability in REACT Learning Assisted by Dynamic Assessment in Terms of Student Learning Independence (Department of Mathematics, Universitas Negeri Semarang, 2022)
Creative and critical thinking abilities and self-directed learning are critical components of mathematical education. This study aimed to ascertain students' capacity to think creatively and mathematically while learning the REACT paradigm through dynamic assessments. This study used a mixed-method approach in conjunction with a sequential explanatory design. The research population consists of students in the seventh grade at SMP Negeri 8 Semarang. The instruments employed are assessments of mathematical creativity, surveys on learning independence, and interview procedures. The findings indicated that (1) students' mathematical creative thinking abilities improved significantly when REACT learning was supported by dynamic assessments; (2) the average mathematical creative thinking ability of students in REACT learning enabled by dynamic assessments is superior to that of students in REACT learning; (3) there is a positive correlation between learning independence and mathematical creative thinking ability; and (4) the description of mathematical creative thinking ability is accurate. Students who demonstrate high learning independence perform admirably on all mathematical creative thinking abilities indicators. Students who have a moderate level of learning independence perform pretty well on the indicators of mathematical creativity. Students with a low level of learning independence demonstrate only one of the three indicators of mathematical creativity.